Analisis Usaha Operasional Lift Net di Teluk Bone, Kabupaten Bone, Sulawesi Selatan - Kurnia Sada Harahap; Muhammad Maskur; Muhammad Sogirun; Mohammad Roin Najih; Bombongan Kusmedy (Jurnal Penelitian Pendidikan IPA, 2024)
The bagan boat is a type of fishing gear that utilizes light to attract schools of fish, either through positive phototaxis or by luring fish searching for food around the light. This method is particularly effective for catching pelagic species such as anchovies, tuna, and squid. This study evaluates the financial feasibility of operating bagan boat fishing gear in Bone Bay, South Sulawesi, through several key financial indicators, including Profit/Loss Analysis, Payback Period (PP), Net Present Value (NPV), and Revenue Cost Ratio (R/C Ratio). The analysis of the operational costs revealed total costs amounting to Rp 487,826,666, which include depreciation, maintenance, and operational expenses. The total revenue generated from the operation was Rp 951,243,999, resulting in a Revenue Cost Ratio (R/C ratio) of 1.95, indicating profitability. The Payback Period (PP) was calculated at 1.56 years, demonstrating a relatively quick return on investment. Additionally, the Net Present Value (NPV) was found to be Rp 1,078,386,238, confirming that the investment generates positive returns. Based on these findings, the operation of bagan boat fishing gear is deemed financially viable, profitable, and sustainable, with strong potential for future growth and development.